Industrial Solid Waste Management for Better Green Supply Chain: Barriers and Motivation - Masrom, N.R.; Abd Rahman, N.A.; Daut, B.A.T. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Moving towards green supply chain activity requires an effective waste management that is applicable and efficient for all industries. The aim of this paper is to find out the barriers and the motivation of the manufacturing companies to implement solid waste management. Barriers are found includes lack of technique and technologies, lack of policy enforcement and responsibility and insufficient of awareness and knowledge. Motivation that led the manufacturing companies to implement solid waste management through encouragement of government, encouragement of non-government organization and socio-psychological incentive. A number of databases in fields such as sociology, social sciences, psychology, and economics were used to acquire literatures on the topic. The findings of the paper include the types of factors that motivate and demotivate the manufacturing companies to implement industrial solid waste management effectively. The paper ends with recommendations on future research on how these factors will help manufacturing companies to implement industrial solid waste management effectively and future research for better environment.